Zakat issues in Muara Teweh, Barito Utara, Kalimantan Tengah - Noor Muhariah Dorojatun; Tjiptohadi Sawarjuwono (Department of Islamic Economics, Islamic University of Indonesia, 2017)
This paper aimed giving information about the development of zakat in Muara Teweh, Barito Utara, Kalimantan Tengah. This paper focused on potrait of zakat management and understanding in Muara Teweh. This paper aimed to describe the potrait development of zakat in Muara Teweh, from the organizations, mustahik, and muzakki than related issues. Method used including observation and documentation through development of zakat in Muara Teweh. The result indicates zakat have applied in Muara Teweh moderately. The issues related to zakat there are zakat activities only really seen when Ramadhan comes, due to the obligation of zakat fitrah for every capable moeslem. The understanding about zakat except zakat fitrah still lack. This impact bought by the mindset of mayority of citizents spending zakat maal as the same time in spending zakat fitrah in Ramadhan month not based on haul and nishab. The minimum amount of socialization and education brough the situation muzakki have a low awareness about zakat and preffer to spend zakat directly to mustahik. Even the zakat management of zakat organizations is still lacking, low awareness and knowledge of muzakki about zakat except zakat fitrah and the mayority of muzakki preffer to spend zakat directly to mustahik but there are activities of zakat seen on Ramadhan month include appealing from Religious Ministry Barito Utara related submission zakat, infaq and sadaqah through Baznas, circulars amount of zakat fitrah and zakat maal, and delivering food packages to mustahik.